The Influence of Employee Performance Assessment and Work Discipline on Job Promotion at PT Graha Bara Lestari Jakarta - Diaz Ayu Ramadhanty; Eli Delvi Yanti; Irvan Malay (Yayasan Multidimensi Kreatif, 2024)
This study aims to find out how employee performance assessments and discipline affect job promotions. PT. Population on study This is all employees of PT Graha Bara Lestari Jakarta totaling 40 respondents. The number of samples taken was 40 respondents. The side technique used was saturated sampling (census). This study was conducted in 2024. Data collection was carried out using a questionnaire to produce primary-quantitative data which is then processed with SPSS version 25 with the method multiple linear regression. The results of the study indicate that the assessment of work performance and employee discipline partially and simultaneously have a positive and significant effect on the promotion of PT Graha Bara Lestari Jakarta. The results of the t-test show that the assessment of work performance has a regression value of 0.311, t-value = 2.081 and significant = 0.000. Employee discipline has a regression value of 0.204 has a t-value = 1.917 and significant = 0.000. The results of the determination coefficient test of 94.7 % of job promotion can be explained and obtained from the assessment of work performance and employee discipline while the rest is influenced by other factors not discussed in this study.